2013
DOI: 10.1016/j.ijporl.2013.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of infant cortical auditory evoked potentials (CAEPs) for tone and speech tokens

Abstract: Objectives Cortical auditory evoked potentials (CAEPs) to tones and speech sounds were obtained in infants to: 1) further knowledge of auditory development above the level of the brainstem during the first year of life; 2) establish CAEP input-output functions for tonal and speech stimuli as a function of stimulus level and to 3) elaborate the data-base that establishes CAEP in infants tested while awake using clinically relevant stimuli, thus providing methodology that would have translation to pediatric audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 68 publications
7
61
0
3
Order By: Relevance
“…Recently published research has revealed an apparent discrepancy between infant tone detection threshold and speech threshold, calling into question whether audibility for one can be used to predict the other (Cone & Whitaker, 2013). It is known that children weight speech-feature cues differently than do adults (Nittrouer 2004; 2007; Nittrouer & Lowenstein, 2007), but exactly how infants process temporal and spectral speech information is not well understood (Berg, 1991; Berg & Boswell, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published research has revealed an apparent discrepancy between infant tone detection threshold and speech threshold, calling into question whether audibility for one can be used to predict the other (Cone & Whitaker, 2013). It is known that children weight speech-feature cues differently than do adults (Nittrouer 2004; 2007; Nittrouer & Lowenstein, 2007), but exactly how infants process temporal and spectral speech information is not well understood (Berg, 1991; Berg & Boswell, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cone & Whitaker (2013) investigated the relationship between perceptual detection thresholds for tonebursts and speech-sound tokens and CAEPs in 36 infants between the ages of 4–12 months. First, CAEP amplitude and latency input-output functions were obtained for tonebursts and speech tokens.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have suggested the name of P1 and N1 to the positive peak and the predominant deflection in the tracing of the infant population. It is believed that from cortical maturation, these components originate the cortical endogenous complex in adults (20) . In order to clarify the effects of maturation of CAEP components, some studies (6,21) indicate the relationship between the variable age and the reduction of latencies of P1 and N1.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the P1-N1-P2 complex suggests that the speech was coded at the level of the auditory cortex and the absence of response is consistent with some imprecision in this process (6,13,14,15) . Some authors have carried out studies on the influence of vowel and consonant speech stimuli on long-latency auditory evoked potentials in children and adults with normal hearing, and could observe that there was influence on the measurements of the components P1, N1, N2 and P3, due to the level of complexity of the speech stimulus (16,17) . Therefore, the hypothesis of this study was to understand how such stimuli influence the generation of auditory evoked potentials and their components.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, because the maturational process is not complete, variations in the response in relation to the acoustic complexity of the speech stimulus and difficulty in its processing are expected (13,14,15,16) . Authors emphasized that using these potentials is important when elicited by speech stimuli, since they allow the monitoring of auditory development in normal children and in children at risk of developing communication disorders and language impairments (17) .…”
Section: Introductionmentioning
confidence: 99%